Chronic bronchial infection and incident cardiovascular events in chronic obstructive pulmonary disease patients: A long‐term observational study. Issue 8 (18th May 2021) - Martinez‐Garcia, Miguel Ángel; Faner, Rosa; Oscullo, Grace; la Rosa‐Carrillo, David; Soler‐Cataluña, Juan Jose; Ballester, Marta; Muriel, Alfonso; Agusti, Alvar
Abstract: Background and objective: Cardiovascular (CV) diseases are frequent in patients with chronic obstructive pulmonary disease (COPD). Likewise, chronic bronchial infection (CBI) is also frequent in COPD and it is associated with systemic inflammation, a well‐known CV risk factor. The objective of this study was to investigate the relationship between CBI, systemic inflammation and incident CV events. Methods: A post hoc analysis of prospectively collected cohort of 201 COPD patients [Global Initiative for Chronic Obstructive Lung Disease (GOLD) II–IV] followed up every 3–6 months for 84 months was conducted. CBI was defined as ≥3 positive pathogenic microorganisms sputum cultures over 1 year, separated by ≥3 months. Systemic inflammation was assessed by circulating levels of C‐reactive protein and fibrinogen. Fatal and non‐fatal CV events, including coronary and cerebrovascular events as well as arrhythmia episodes, were prospectively recorded. For analysis, they were analysed separately and combined in a composite variable. Results: As hypothesized, CBI was associated with persistent systemic inflammation and a significantly higher incidence of CV events (HR: 3.88; 95% CI: 1.83–8.22), mainly of coronary origin independent of age, number and severity of exacerbations, comorbidities, other CV risk factors, lung function, BMI, smoking status and treatments. These associations were particularly significant in patients with CBI by Pseudomonas aeruginosa (PA). Conclusion: CBI, particularly by PA, is associated with sustained and enhanced systemic inflammation and a higher incidence of CV events (especially coronary events). The possibility that treating CBI may decrease systemic inflammation and CV events in COPD deserves prospective, interventional studies. Abstract : Chronic bronchial infection, particularly by Pseudomonas aeruginosa, is associated with increased persistent systemic inflammation and a higher incidence of fatal and non‐fatal cardiovascular (CV) events, especially coronary ones, independent of other well‐established CV risk factors.